Knowledge Management education in the departments of Library/Information Science in South Africa - Ondari, Ezra Okemwa; Minishi-Majanja, Mabel K. (Sabinet, 2007)
This paper focuses on the role of the departments of Library and/or Information Science (U1S) in South African universities in the training of Knowledge Management (KM) competencies. A questionnaire was e-mailed to thirteen L/IS departments. of which 9 (69%) responded. All respondents showed great interest in KM as an U1S competency. They all view KM as legitimately belonging to L/IS because of the long involvement in the organization of information and knowledge. However, only 7 of these departments are currently offering some KM subjects. but with marked differences in the scope. level and stages of development towards offering KM noted among the departments. The choice of subjects taught is not necessarily what any manager perse would need. but rather what an information manager would need to be successfully integrated in a business management setup. Moreover. this choice of subjects hos evolved based on what the offering department views as the core of KM as well as what available expertise is able to provide.